(untitled) (Моделювання, керування та інформаційні технології, 2019)
The paper suggests an approach to modelling the electrocoagulation process taking into account the ratio between the values of the parameters which characterize the domination of convective and mass-exchange components of the process over diffusion. Computer simulation of the distribution of iron concentration inside the electrocoagulator that allows predicting various hydrodynamic phenomena such as internal recirculation that affects the formation of a coagulant was conducted